InGaN/GaN dot‐in‐a‐wire: ultimate terahertz nanostructure. Issue 1 (2nd January 2015) - Sun, Guan; Chen, Ruolin; Ding, Yujie J.; Nguyen, Hieu P. T.; Mi, Zetian
<x xml:space="preserve">Abstract</x> Terahertz radiation from nitride‐based dot‐in‐a‐wire nanostructures is investigated. Sub‐micro‐watt terahertz signal is generated with just ten vertically‐stacked quantum dots in each nanowire. A single quantum wire is capable of generating 10 pW, corresponding to 1 pW per dot. By applying a reverse bias along the wires in a light emitting device consisting of such nanostructures, the THz output power is increased more than fourfold. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>